(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In the second half of the seventeenth century in the Hacienda named Jorullo, owned by Joseph Andres Pimentel, perpetual governor of the city of Patzcuaro, the Jorullo volcano erupted. This phenomenon led to a strong economic and social impact that was manifested in economic and material losses from the destruction of a significant portion of large estates and fields. The birth of the volcano also affected the entire population, especially to those who lost their homes and crops, forcing them to move. Some of them went to neighboring towns like Churumuco and Tamacuaro because the damage caused by the volcano was extensive. As a result of the consequent natural disaster, economic recovery in certain areas and haciendas was very slow and so the landowners of the region used the eruption as a pretext for evading the payment of taxes to the Church and the Royal Treasury.